Muscle Fiber and Performance Changes after Fast Eccentric Complex Training. - Bogdanis, Gregory C; Tsoukos, Athanasios; Brown, Lee E; Selima, Elisavet; Veligekas, Panagiotis; Spengos, Konstantinos; Terzis, Gerasimos (Med Sci Sports Exerc, 2018)
INTRODUCTION: The purpose of this study was to examine the effects of a short-term fast eccentric and ballistic complex training program on muscle power, rate of force development (RFD), muscle fiber composition, and cross-sectional area (CSA). METHODS: Sixteen male physical education students were randomly assigned to either a training group (TG, n = 8) or a control group (n = 8). The TG followed a 6-wk low volume training program, including fast eccentric squat training with an individually optimized load of 74% ± 7% of maximal half-squat strength (1RM) twice per week and a ballistic training session with loaded (30% 1RM) and unloaded jump squats, once per week, all combined with unloaded plyometric jumps. RESULTS: Half squat 1RM was increased in the TG from 1.87 ± 0.28 to 2.14 ± 0.31 kg per kilogram body mass (14.4% ± 9.3%, P = 0.01). The percentage of types I, IIA, and IIX fibers were similar in the two groups at pretesting and did not change after the intervention period (P = 0.53-0.89). Muscle fiber CSA increased in all fiber types by 8.3% to 11.6% (P = 0.02 to 0.001) in TG only. Countermovement jump height and peak power measured at five different external loads (0%-65% of 1RM) only increased in the TG by approximately 20% to 36% (P < 0.01) and approximately 16% to 22% (P < 0.01), respectively. Peak ground reaction force during jump squats remained unchanged in both groups, whereas RFD increased in the TG only (40%-107%, P = 0.001). CONCLUSIONS: A combination of low-volume fast eccentric and ballistic jump squat training with plyometric jumps in a strength-power potentiation complex format, induced substantial increases in peak leg muscle power, RFD, and maximal strength, accompanied by gains in CSA of all muscle fiber types, without a reduction in fast twitch fiber composition.